2022
DOI: 10.1097/tp.0000000000004266
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Renal Function in Living Kidney Donors and Recipients of Living Donor Kidneys Using Quantitative Histology

Abstract: Background. Living kidney donors (LKDs) are at increased risk of chronic kidney disease, whereas transplant recipients experience progressive reduction of graft function. We examined the predictive value of quantitative stereology on renal function in LKDs and recipients of living donor kidneys, based on perioperative biopsies from the donated kidney. Methods. Cortex volume of both donor kidneys was determined by contrast-enhanced computed tomography and single-kidney glomerular filtration rate (GFR) by 51ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Total GFR is the result of single nephron GFR and number of nephrons [ 2 ], so it would be interesting for future studies to investigate whether PTC density is in fact related to single-nephron GFR, and whether this explains the lack of an association with total GFR in healthy kidneys. Our finding that IF/TA in the pre-donation biopsy is not related to measured GFR post-donation confirms results from Buus et al [ 30 ]. We observed that individuals with more than 5% IF/TA had an increased tubular area and (a trend towards) a larger glomerular volume.…”
Section: Discussionsupporting
confidence: 92%
“…Total GFR is the result of single nephron GFR and number of nephrons [ 2 ], so it would be interesting for future studies to investigate whether PTC density is in fact related to single-nephron GFR, and whether this explains the lack of an association with total GFR in healthy kidneys. Our finding that IF/TA in the pre-donation biopsy is not related to measured GFR post-donation confirms results from Buus et al [ 30 ]. We observed that individuals with more than 5% IF/TA had an increased tubular area and (a trend towards) a larger glomerular volume.…”
Section: Discussionsupporting
confidence: 92%